Study of the formation effect of the cubic phase of LiTiO2 on the structural, optical, and mechanical properties of Li2±xTi1±xO3 ceramics with different contents of the X component - Shlimas, D. I.; Kozlovskiy, A. L.; Zdorovets, M. V. (Journal of materials science. Materials in electronics, 2021)
The paper presents the results of the study of structural, morphological, optical, and mechanical properties of lithium-containing ceramics obtained using the method of mechanochemical solid-phase synthesis. The purpose of this work is to assess the possibility of obtaining lithium-containing ceramics of the two-phase type, as well as the formation effect of the cubic phase of LiTiO 2 on changes in the properties of ceramics. The relevance of this study is to obtain new data on the properties of lithium-containing ceramics, which have great prospects in their use as blanket materials for tritium reproduction. During the study, it was found that the formation of the LiTiO 2 cubic phase leads to a change in the morphological features of ceramics, with the formation of sphere-like agglomerates of a nanoscale scale. An increase in the contribution of the LiTiO 2 phase leads to a shift of the fundamental absorption edge, as well as the appearance of additional absorption bands. During mechanical tests for the determination of resistance to destruction by single compression, it was found that an increase in ceramic density, which is due to an increase in the contribution of the cubic phase, leads to an increase in resistance by 70–85%.